Key issues to consider in the renewal of learning and teaching experiences to foster Graduate Attributes. - Barrie, Simon; Smith, Calvin; Hughes, Clair; Thomson, Kate (Australian Learning and Teaching Council (ALTC), 2009)
Graduate attributes have received considerable attention in recent years as universities seek to renew and articulate their purposes and as governments and external professional bodies, nationally and internationally, seek to develop outcomes-based quality assurance and accreditation processes for higher education. As discussions concerning ‘assuring standards of learning’ intensify in Australia and internationally, the definition, development and assurance of graduate attributes will become increasingly important to universities’ missions and success. Most importantly they will be increasingly important for students as a focus for a renewal of teaching and learning experiences as our society looks to universities to educate graduates for a challenging and changing world. Eight issues to consider in the renewal of learning and teaching experiences to foster graduate attributesThe framework described in this set of ‘issues papers’ is one of the products of a national scoping study of Australian universities’ recent activities in relation to the development of graduate attributes. The study was called the National GAP (Graduate Attributes Project) and was funded by the Australian Learning and Teaching Council in 2007 - 2008. [Publisher summary, ed]